Penerapan Artificial Intelligence (AI) untuk Penerbitan Fatwa dalam Perspektif Hifzh Al-Din - Ilham Ilham (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
The development of artificial intelligence (AI) technology had a significant impact across various fields, including Islamic law. The use of AI in issuing fatwas emerged as a phenomenon that required serious attention from Muslim scholars. This study aimed to examine the legal ruling on the use of AI in the fatwa-issuing process through the perspective of Maqasid Sharia, with particular emphasis on Hifzh al-din (the protection of religion). The research focused on addressing the main question: how Maqasid Sharia viewed the utilization of AI in seeking fatwas. This study employed library research with a qualitative approach, drawing on sources such as books, scholarly articles, and other relevant documents. The findings indicated that although AI had the capability to process and analyze data efficiently, its use had to be confined within the framework of Islamic law. AI could not replace the role of the mufti due to its limitations in understanding context, ethics, and deeper spiritual values. Islam did not reject technological advancement as long as it did not contradict religious principles. Therefore, AI could be used as a supporting tool in the fatwa-issuing process, but was not positioned as a primary source of legal authority. The prudent and well-directed use of AI was expected to enhance the effectiveness of decision-making without neglecting the five core principles of Maqasid Sharia: the protection of religion, life, intellect, lineage, and property.